Implementasi Modul Matematika dengan Pembelajaran Time Token untuk Meningkatkan Kognitif Komprehensif dan Problem Solving Siswa - Netriwati, Netriwati; Permata, Aulia Diva; Ramadalia, Ramadalia; Zilfhadila, Meydira; Yulianto, Yulianto (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to examine the effect of the time token learning model on improving students' comprehensive cognitive abilities and problem-solving skills on the topic of circles. This study was motivated by the suboptimal utilization of learning modules, as well as the lack of innovation in mathematics learning models that impact students' low engagement and thinking skills. The research method used was a quasi-experimental design with a pretest-posttest two treatment groups. The sample of the study was 45 eighth grade students. The research instrument was an essay test analyzed using N-Gain to measure improvements in comprehensive cognitive abilities and problem-solving, and MANOVA test to see differences between groups. The results showed that the application of the time token learning model was able to improve students' comprehensive cognitive abilities and problem-solving in the medium category. The N-Gain values ​​in large groups were 0.520 and 0.359, respectively, while in small groups were 0.558 and 0.342. However, the results of the MANOVA test showed that there was no significant effect of group size on both abilities. The main findings of this study indicate that the time token model is effective in improving students' abilities, but differences in group size (small and large) did not have a significant effect. This model also encourages active participation and equitable student involvement in mathematics learning.